1999
DOI: 10.1091/mbc.10.12.4135
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Heterodimeric Amino Acid Transporter Defective in Cystinuria

Abstract: Mutations of the glycoprotein rBAT cause cystinuria type I, an autosomal recessive failure of dibasic amino acid transport (b0,+ type) across luminal membranes of intestine and kidney cells. Here we identify the permease-like protein b0,+AT as the catalytic subunit that associates by a disulfide bond with rBAT to form a hetero-oligomeric b0,+amino acid transporter complex. We demonstrate its b0,+-type amino acid transport kinetics using a heterodimeric fusion construct and show its luminal brush border localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
146
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(155 citation statements)
references
References 39 publications
9
146
0
Order By: Relevance
“…Laser scanning confocal microscopic analyses demonstrated that b 0,ϩ AT and rBAT colocalized on the apical plasma membrane of the b 0,ϩ AT-rBAT transfectants. This distribution reflects the normal localization of these transport proteins in proximal tubular cells in vivo (13)(14)(15). Cotransfection of MDCK II cells with these two subunits resulted in a gain of function, which was evidenced by a 10-fold increase in the V max for the transport of cystine.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Laser scanning confocal microscopic analyses demonstrated that b 0,ϩ AT and rBAT colocalized on the apical plasma membrane of the b 0,ϩ AT-rBAT transfectants. This distribution reflects the normal localization of these transport proteins in proximal tubular cells in vivo (13)(14)(15). Cotransfection of MDCK II cells with these two subunits resulted in a gain of function, which was evidenced by a 10-fold increase in the V max for the transport of cystine.…”
Section: Discussionmentioning
confidence: 65%
“…transporter is known to transport cystine and is localized to the luminal plasma membrane of the target epithelial cells, i.e., proximal tubular cells (2,(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two heteromeric amino acid transport exchangers (systems b o,ϩ and y ϩ L) have a major role in the reabsorption of cystine and dibasic amino acids (2)(3)(4). First, the heterodimer formed by rBAT and b o,ϩ AT is the amino acid transporter b o,ϩ , which mediates high-affinity uptake of cystine and dibasic amino acids coupled with the efflux of neutral amino acids (5)(6)(7)(8) at the apical membrane of epithelial cells of the proximal tubule (9). Indeed, mutations in the rBAT (SLC3A1) gene cause type I cystinuria, and mutations in the b o,ϩ AT (SLC7A9) gene cause mainly non-type I and also type I cystinuria (recessive inherited aminoacidurias of cystine and dibasic amino acids) (6,10,11).…”
mentioning
confidence: 99%
“…Uptakes-Oocyte preparation and cRNA injection were carried out according to previously described procedures (8,10). Briefly, injected oocytes were incubated for 72 h in ND96 buffer (96 mM NaCl, 2 mM KCl, 1 mM MgCl 2 , 1 mM CaCl 2 , and 10 mM HEPES, pH 7.4, adjusted with KOH) supplemented with tetracycline (50 mg/l).…”
Section: Functional Experiments In Xenopus Laevis Oocytes-mentioning
confidence: 99%